Rough contact of sliding viscoelastic layers: numerical calculations and theoretical predictions. (June 2018) - Menga, N.; Afferrante, L.; Demelio, G.P.; Carbone, G.
Abstract: We study the sliding contact of viscoelastic layers on rigid rough profiles, with two different contact configurations: constrained on the upper boundary, and uniformly loaded on the top. Results show that layer thickness and boundary conditions affect both the average contact quantities and the viscoelastic friction. Interestingly, the latter is strongly influenced by the specific controlled parameter. Under displacement controlled conditions, large differences are observed in the frictional behavior of the two contact configurations. Conversely, in load control, the friction coefficient is almost independent of the specific boundary condition. Finally, a comparison with a 1D version of the Persson's theory is proposed, finding a good agreement in terms of contact area and friction coefficient dependence on the sliding velocity. Highlights: Boundary conditions effects on viscoelastic layer in sliding contact is investigated. Under load controlled conditions friction is not affected by boundary conditions. Persson's theory predictions are in good agreement with the numerical calculations.